Effects of Supply and Commodity Substitution on Chili Price Volatility at Kramat Jati Wholesale Market, Jakarta, Indonesia - Wasita, Rendra; Hidayat, Nia Kurniawati; Suprehatin, Suprehatin (Universitas Panji Sakti, 2025)
Chili commodity production has been rising and falling over the years. In contrast, prices for chili experience extreme variability. A price fluctuation of more than 40% indicates that something is wrong with supply management. Chili price volatility poses significant challenges for food security and inflation control in Indonesia. This study investigates the factors influencing cayenne pepper prices using daily data from January 2023 to September 2024 at the Kramat Jati Wholesale Market. An Autoregressive Distributed Lag (ARDL) model was applied to estimate the dynamic relationship between prices and supplies of cayenne and curly red chili. The results indicate that previous prices, substitution effects with curly red chili, and supply shocks have a significant influence on cayenne pepper prices. These findings underscore the importance of real-time supply monitoring, market integration, and strategic distribution planning in mitigating price spikes. The study offers empirical evidence to support more responsive government interventions in stabilizing chili prices and reducing inflationary pressure in perishable food markets.